The Possibility of Expanding the Implementation of Local Political Party Systems in Indonesia: Posibilitas Perluasan Penerapan Sistem Partai Politik Lokal di Indonesia - Caesario, Wibisena; Haryanto, Muhammad Kevin Setio (Lex Renaissance, 2025)
The party and electoral system in Indonesia has experienced developments, one of which is the birth of local political parties. Regulations regarding local political parties have only been accommodated for Aceh Province. Of course, this is inseparable from the position of the two provinces that hold special autonomy. On the other hand, there is also a close correlation between the existence of local political parties and regional autonomy, even indirectly connected through the constitution. Therefore, the author intends to analyze two things, namely (1) how is the status quo of the existence of local political parties in Indonesia? (2) how is the possibility of expanding the application of local political parties in Indonesia? This research is normative legal research using literature study. As a result, there are juridical, sociological, political, and historical factors behind the existence of local political parties. This also what makes the existence of local political parties in Aceh stronger. There is the possibility of implementing a local political party system widely because it can strengthen regional autonomy that prioritizes the aspirations of local communities and eliminates dependence on the center. However, there are challenges related to identity politics and changes in the relationship between the center and the regions that could potentially conflict with the unitary state system.